GP's understanding of the benefits and harms of treatments for long-term conditions: An online survey - Treadwell, J; Wong, G; Milburn-Curtis, C; Feakins, B; Greenhalgh, P (Royal College of General Practitioners, 2020)
Background: GPs prescribe multiple long-term treatments to their patients. For shared clinical decision-making, understanding of the absolute benefits and harms of individual treatments is needed. International evidence shows that doctors’ knowledge of treatment effects is poor but, to the authors knowledge, this has not been researched among GPs in the UK.